Pengaruh Pendidikan Kesehatan Tentang Menstruasi Terhadap Tingkat Kecemasan Pada Siswi di SD Negeri 25 Manado - Frischa Ellyanti Djenaan; Merry H. Rimporok; Sri Wahyuni (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Menstruation is the decay of the uterine wall consisting of blood and body tissues. These events take place every month and are a normal process for ordinary women. Menstruation is periodic bleeding in the uterus that begins about 14 days after ovulation. The purpose of this study was to determine the Effect of Health Education About Menstruation on Anxiety Levels in Students at SD Negeri 25 Manado. This research method uses a Pre-experimental design with the One Group Pre test – Post test design method. Subjekts in this study amounted to 49 female students with a sample of 15 female students. The sampling technique in this study used stratified random sampling and research instruments using questionnaires, this study used the Wilcoxon test. The Wilcoxone test showed a Sig. (2-tailed) value of 0.001 that the Wilcoxon test results between pre test and post test had a significant value of 0.001 smaller than the value of α= 0.05. The conclusion in this study was the effect of health education about menstruation on anxiety levels in female students with Wilcoxon test results p = 0.001. This p value is smaller than the value of α= 0.05, so health education about menstruation is very influential on female students who experience menstruation.